Social Value in Social Activities of Banjar and Arab Communities in Pekauman Ulu Village - Azizah, Nur; Abbas, Ersis Warmansyah; Handy, Muhammad Rezky Noor; Mutiani, Mutiani; Ilhami, M. Ridha (Universitas Lambung Mangkurat, 2024)
Social Values are a benchmark for assessing a person's or society's attitudes which are believed to be something that is considered good. There are various kinds of social values, both in daily life and in community activities. Pekauman Ulu Village is a village located in East Martapura District, Banjar Regency, it is a village in which there are various kinds of communities, such as the Banjar community and the Arab community. The Banjar and Arab communities certainly have differences in terms of habits, race and culture. These differences make the Banjar and Arab communities respect each other and value each other, from these differences the social activities that occur in Pekauman Ulu village are created. These activities, such as weddings, matrimonial recitations and social gatherings, from the activities that occur in Pekauman Ulu village give rise to social values, namely the value of cooperation, the value of tolerance, the value of helping each other and also the value of harmony between communities.